CURRENT CHALLENGES IN WRITING SKILLS INSTRUCTION AND THEIR IMPLICATIONS FOR FORENSIC HANDWRITING ANALYSIS - E. Belova (Теория и практика судебной экспертизы)
The paper describes methods for teaching writing skills and types of writing workbooks currently used in schools. A handwriting study was conducted among 2nd-to-4th graders, 7th-to-9th graders, and 1st-to-3rd year students of vocational colleges. The author anticipates how current conditions of writing skills acquisition may aﬀect evolving forensic handwriting analysis techniques, as well as possible changes in forensic handwriting analysis caseload.